Endoscopic Retrograde Cholangiopancreatography followed by Laparoscopic Cholecystectomy versus Laparacosopic Cholecystectomy and Common Bile Duct Exploration in Concomitant Gallstone and Common Bile Duct Stone - Stefanus Satrio Ranty; Anggilia Stephanie; E Mudjaddid; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2016)
Aim: Cholecystolithiasis is frequently accompanied with choledocholithiasis, with the incidence ranged from 8-20%. The current management of concomitant cholecystolithiasis and choledocholithiasis is varied, either Endoscopic Retrograde Cholangiopancreatography (ERCP) followed by Laparoscopic Cholecystectomy (LC) or LC followed by ERCP, or single-step procedure, i.e. LC with common bile duct exploration (LCBDE). This evidence-based case report (EBCR) will compare the efficacy, effectiveness, and safety between the ERCP+LC and LCBDE.Method: The article search was done through PubMed, EBSCO, dan Cochrane at 1st December 2015 using keywords ERCP, LC, gallstone, common bile duct. Two meta-analyses and two randomized clinical trial were found and critical appraisal was done to all four articles.Results: All four studies showed similar stone clearance for both procedures. One meta-analysis showed better clearance in single procedure (OR = 1,56; 95% CI: 1,05-2,33; p: 0,03; heterogeneity: I2 = 42%). Mortality and morbidity rate, complication, and the need of another procedure were no difference between single-step and two-step procedure. Length of stay and cost effectiveness were better in single-step procedure in all studies.Conclusion: Single-step procedure may show better result in stone clearance, cost-effectiveness, and length of stay. However, this procedure may be limited, thus can only be done in health center with sufficient resources. ERCP followed by LC is still the preferred procedure, especially in patient with worse performance status and limited health center.